2020
DOI: 10.1007/s00417-020-04777-7
|View full text |Cite
|
Sign up to set email alerts
|

Ocular manifestations of coronavirus disease 2019

Abstract: Purpose Coronavirus disease 2019 (COVID-19) is an ongoing global public health problem, and most of the COVID-19 research is focused mainly on the respiratory system because of life-threatening results. However, manifestations in other organs should not be ignored since they can also be a mode of transmission. We sought to describe the ocular manifestations of COVID-19 and investigate the association between ocular involvement and clinical presentation and laboratory outcomes. Methods This cross-sectional stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 28 publications
0
65
1
6
Order By: Relevance
“…18 Cheema et al reported a case of keratoconjunctivitis with corneal subepithelial infiltrates and overlying epithelial defects. 19 Other ocular manifestations include photophobia, 20 redness, ocular secretions, chemosis, itching, foreign body sensation, dry eyes, follicular conjunctivitis, and episcleritis 21 (summarized in Table 1). Importantly, none of the studies reported any associated changes in visual acuity of COVID-19 patients with ocular manifestations.…”
Section: Ocular Manifestations Of Covid-19mentioning
confidence: 99%
“…18 Cheema et al reported a case of keratoconjunctivitis with corneal subepithelial infiltrates and overlying epithelial defects. 19 Other ocular manifestations include photophobia, 20 redness, ocular secretions, chemosis, itching, foreign body sensation, dry eyes, follicular conjunctivitis, and episcleritis 21 (summarized in Table 1). Importantly, none of the studies reported any associated changes in visual acuity of COVID-19 patients with ocular manifestations.…”
Section: Ocular Manifestations Of Covid-19mentioning
confidence: 99%
“…Responses of individual patients can vary widely, from asymptomatic or mild disease to multi-organ failure and death. 4 Accumulating evidence suggests that COVID-19 can impact many bodily systems that encompass respiratory, 5 immunologic, 4 gastrointestinal, 6 ocular, 7 urologic, 8 hepatic, 9 dermatologic, 10 neurologic, 11 and psychiatric 12 effects. To help people determine whether they might have COVID-19, leading health information providers list symptoms of COVID-19 online.…”
Section: Introductionmentioning
confidence: 99%
“… 14 Bostanci Ceran et al investigated the ocular findings of confirmed COVID-19 cases and found that 2 out of 93 patients had episcleritis. 15 In addition, Lu et al 7 discuss the case of Dr Guangfa Wang who, while working with COVID-19 patients complained of red eyes a few days before the onset of COVID-19 symptoms. The fact that he had been wearing an N95 mask but no eye protection gave rise to concerns that the infection may have gained entry via his ocular route.…”
Section: Discussionmentioning
confidence: 99%